Made By Singapore : rediscovering the meaning behind local fashion - Tan, Janessa Hui En (Nanyang Technological University, 2022)
This paper presents Made By Singapore, an integrated communication campaign aimed at raising awareness, improving sentiment and driving purchase of local fashion brands among working professionals in the marketing and communication industry aged 25 to 40. The campaign succeeds last year’s FYP project Made By Singapore, which had a similar objective but focused on a younger target audience. To uncover the true value that local fashion brings, the campaign was anchored on five concepts: fashion as celebration, heritage, commitment, creativity and empowerment. Spotlighting stakeholders within the local fashion scene inclusive and beyond the commercial sector, the campaign was largely run on Facebook and Instagram, with an offline engagement. The campaign surpassed its objective of a 30% increase in awareness of local fashion brands, a 0.30 improvement on a 5-point Likert Scale on perceptions that local fashion is value-for-money and fashionable. However, the objectives of improving the sentiment that local fashion has variety and the behavioural objective of a 10 percentage point increase in purchases were not met. This paper will cover the formative research, campaign development, execution, implementation and explore limitations and recommendations. The paper includes the key data relevant to our campaign while all other documents and research data can be found in the Appendix.